Unravelling Societal Constructs and Feminine Agency: A Critical Analysis of Manju Kapur’s Difficult Daughters - Sanap, Sarala Kisan (Integrated Journal for Research in Arts and Humanities, 2024)
Manju Kapur's Difficult Daughters stands as a pivotal work in the realm of Indian English literature, delving into the intricate complexities of familial dynamics, societal norms, and individual agency against the backdrop of pre-partition Punjab. This research article aims to explore Kapur's narrative through a critical lens, dissecting themes of tradition, rebellion, and the quest for identity within the context of a patriarchal society. By examining the characters' struggles and triumphs, this study seeks to unravel the multifaceted layers of gender roles and societal expectations depicted in the novel. Through a combination of literary analysis and sociocultural critique, this research endeavors to shed light on the enduring relevance of "Difficult Daughters" in contemporary discourse on gender, tradition, and autonomy.